HAK AZASI MANUSIA ANAK DALAM PERSPEKTIF HUKUM ISLAM - Nurhadi Nurhadi; Rizizhco Ardianto Murti (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2018)
Indonesia from the norm, categorized countries with commitments in the HUMAN RIGHTS of children. This research aims to mengetahuai how the concept of HUMAN RIGHTS of the child according to law No. 17 Th 2016 and Islam?. This qualitative research study mixed with primary sources of LAW No. 17 Th 2016 and Islamic Fiqh Wa Adillatuhu Wahbah Juhaili and other supporters. Research results: 1). The concept of the HUMAN RIGHTS of children in law No. 17 Th 2016 on the protection of the child, that the perlindunagn against an absolute must do because starting from the international and national level already has a strong legal instrument, especially the law of Pidananya, namely article I number 1 with imprisonment the shortest 5 (five) years and the longest 15 (fifteen) years and a maximum fine of Rp 5,000,000,000.00 (five billion dollars), then the identity of the perpetrators in the halayak crowded in front of the post, was also castrated chemistry as well as the installation of electronic detection tools. 2). children's HUMAN RIGHTS Concepts in Islam include: 1). Right to life; 2. name); 3). Aqiqah; 4). BREAST MILK; 5). Eat Drink; 6). Rizqi; 7). Islamic Studies 8). The Bed; 9). Instruction Read Write; 13.) health care; 14). Teaching skills; 15.) a good place in the hearts of Parents; 16). Compassion; 17). Protection in political activities, the involvement of disputes, Wars, riots and violence; 18.) are not Exploited, economic and Sexual; 19). The protection and legal assistance; Punishment is appropriate and Humane.